Recent Advances in Deep Learning Techniques - Sornam, M; Selvam, E. Panneer (International Journal of Computer Sciences and Engineering, 2025)
Deep Learning is currently being used for a variety of different applications. It has drawn increasing research interest because of the capability of overcoming the drawback of traditional algorithms. Some of the important applications are pattern recognition, computer vision, speech recognition, natural language processing, handwriting recognition, face recognition, IoT and medical. There are several researches has been done in the area of deep learning from the last decade of the nineteenth century and still many more to come. This paper gives survey on deep learning and some of the recent research that has been done in the area of deep learning